The Influence of Fear of Missing Out (FOMO), Viral Marketing, Hedonic Lifestyle, Discount Strategies, and Sales Promotion Intensity on Impulse Buying Behavior Among Makeup Users in Bandar Lampung - Maura Zafasha; Lestari Wuryanti; Ayu Nursari (International Journal of Management, Economic and Accounting, 2026)
This study aims to test and analyze the influence of Fear of Missing Out (FOMO), viral marketing, hedonistic lifestyle, discount strategies, and sales promotion intensity on impulse buying behavior in makeup users in Bandar Lampung. The population in this study includes all private university students in Bandar Lampung totaling 24,631 people, of which 100 respondents were selected as a sample using purposive sampling techniques. A quantitative approach was applied by collecting primary data through questionnaires, which were then analyzed using multiple linear regression methods with the help of SPSS software. The results of the analysis showed that partially, the variables of FOMO, viral marketing, hedonistic lifestyle, and the intensity of sales promotions had a positive and significant effect on impulse buying. Conversely, the research findings also revealed that discount strategies have a negative and significant influence on these behaviors. Simultaneously, the five independent variables were shown to be able to explain the variation in impulse buying behavior very well. This study provides practical recommendations for cosmetics business actors to further maximize the approach of consumer psychological factors and digital promotion, while avoiding giving excessive discounts that can actually trigger skepticism about product quality.